2015
DOI: 10.1111/1753-0407.12279
|View full text |Cite
|
Sign up to set email alerts
|

Review of gastroesophageal reflux disease (GERD) in the diabetic patient

Abstract: This article reviews the known pathophysiological mechanisms of comorbid gastroesophageal reflux disease (GERD) in the diabetic patient, discusses therapeutic options in care, and provides an approach to its evaluation and management. We searched for review articles published in the past 10 years through a PubMed search using the filters diabetes mellitus, GERD, pathophysiology, and management. The search only yielded a handful of articles, so we independently included relevant studies from these review articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 88 publications
(190 reference statements)
0
27
0
4
Order By: Relevance
“…GERD is associated with DM, which indicates that DM likely also affects the LES and the EGJ. Motor dysfunctions of the UES and LES in DM have indeed been demonstrated .…”
Section: Diabetes‐induced Remodeling In the Esophagusmentioning
confidence: 99%
See 3 more Smart Citations
“…GERD is associated with DM, which indicates that DM likely also affects the LES and the EGJ. Motor dysfunctions of the UES and LES in DM have indeed been demonstrated .…”
Section: Diabetes‐induced Remodeling In the Esophagusmentioning
confidence: 99%
“…GERD is one of the most common upper‐GI disorders in the Western world . The changing dietary patterns and global increase in obesity have led to an increase in GERD in previously low‐incidence regions . Although conflicting data for evaluating the relationship between DM and GERD have been reported, recent reviews have demonstrated that diabetic patients are at greater risk of GERD than those who do not have DM .…”
Section: Clinical Consequences Of Diabetes‐induced Changes In the Esomentioning
confidence: 99%
See 2 more Smart Citations
“…Drugs that alter gastric pH are commonly used by patients with T2DM, and they therefore have the potential to be coadministered with saxagliptin. Saxagliptin has high aqueous solubility relative to its usual dose of up to 5 mg.…”
mentioning
confidence: 99%